Wisconsin's Nazi Resistance the Mildred Fish-Harnack story - Kaczmarek, Jane (Wisconsin Public Television, 2011)
In 1933 Adolf Hitler seized control of Germany, but not all Germans were captivated by his spell. Mildred Fish-Harnack was a Milwaukee-born, University of Wisconsin-Madison graduate living under the Nazi regime. Along with her German husband, Arvid, she chose to fight back. For nine years, they were part of a world of resistance and espionage providing information to Hitler's enemies in America and the Soviet Union. The stakes were incredibly high , and a twist of fate set them on a collision course with Hitler. -- container